The effect on artery clamp for dehorning cattle - Drake, C.L.; Smith, C.W. (Kansas Agricultural Experiment Station, 2011)
Forty horned yearling heifers owned and fed by a cooperating feeder were used. Allotment was by gate cut into four groups of 10 each. Each group was weighed before being dehorned. Treatments follow: 1.) Control-not dehorned. 2.) Dehorned using clamp; arteries pulled. 3.) Dehorned without dehorning clamp; arteries pulled. 4.) Dehorned without dehorning clamp; arteries not pulled. After one hour, bleeding from several animals was so severe that dehorning clamps were used and arteries were pulled. All cattle were placed in on large lot and fed the same ration. The trial lasted 22 days.
Keywords: Beef; Artery clamp; Dehorning cattle